Telbivudine in chronic lymphocytic myocarditis and human parvovirus B19 transcriptional activity - Van Linthout, Sophie (ESC Heart Fail, 2018)
AIMS: Myocarditis is often associated with parvovirus B19 (B19V) persistence, which can induce vascular damage. Based on the antiviral and anti‐inflammatory properties of telbivudine, we aimed to evaluate its efficacy to protect B19V‐infected endothelial cells in vitro and to treat chronic lymphocytic myocarditis patients with B19V transcriptional activity. METHODS AND RESULTS: We evaluated the endothelial‐protective potential of telbivudine in human microvascular endothelial cells‐1, which were infected with B19V. Treatment with 10 ng/mL of telbivudine decreased the B19V‐induced endothelial cell apoptosis and endothelial‐to‐mesenchymal transition. Along with this finding, telbivudine reduced the expression of transforming growth factor‐β1 and of tenascin‐C. The endothelial‐protective properties of telbivudine were also found in tumour necrosis factor‐α‐stressed human microvascular endothelial cells‐1. In addition, oxidative stress in angiotensin II‐stressed and transforming growth factor‐β1‐stressed HL‐1 cardiomyocytes and fibroblasts, respectively, was reduced upon telbivudine treatment, illustrating that telbivudine exerts multimodal protective effects. Based on these in vitro findings, four patients severely suffering from an endomyocardial biopsy‐proven myocarditis associated with B19V transcriptional activity (VP1/VP2‐mRNA positive) were treated with telbivudine (600 mg/dL) for 6 months in a single‐patient‐use approach. Follow‐up biopsies 6 months after treatment showed that VP1/VP2‐mRNA levels and CD3 cells decreased in all patients and were associated with an improvement in ejection fraction and New York Heart Association class. These findings were paralleled by a drop in tenascin‐C expression as shown via matrix‐assisted laser desorption ionization–imaging mass spectrometry. CONCLUSIONS: Telbivudine exerts endothelial‐protective effects in B19V‐infected endothelial cells and improves chronic myocarditis associated with B19V transcriptional activity. These findings will be further evaluated in the clinical exploratory trial: the PreTopic study.